Simulação numérica do reinício de escoamento de fluido de perfuração gelificado - Silva, Hiago Souza da (2023)
During the oil well drilling, a pressure gradient develops along the well. This gradient needs to be carefully controlled, since the well only accepts a narrow operational pressure interval. Such pressures are difficult to measure, therefore, they are usually estimated by numerical simulation. To assure reliability to the process, the prediction methods must be as precise as possible. In this context, the mathematical models employed have central role. The drilling fluid itself requires considerable complexity for the modelling, specifically because of its elasticviscoplastic behavior. Transient effects in the flow also have maximum relevance, and are essential to take into account. The main goal of this work is to develop a mathematical model to describe the start-up flow of gelled drilling fluids. The model is composed by the equations of mass and momentum balance, equation of state and the thixotropy model equation. The geometry of the problem consists in a horizontal pipe, with the flow being taken as onedimensional, transient and compressible. The thixotropy model relies on the unbalance between the equilibrium viscosity and the current viscosity. Mass and momentum equations are coupled and solved by the Method of Characteristics. The kinetic equation of the model was compared with experimental results from rheometric tests over drilling fluid, and a good agreement was reached after the parameters fitting. From the sensitivity analysis, it was observed the dissipative character of the problem, as well as the influence of the fluid inertia as an advancer or a retardant of the gelled fluid break-up. The gel break mechanism is represented as the change in the velocity plateau, which results in the pressure variation: after the local gel breakage, pressure rises until the full break, when it starts to relieve, until its steady state.